Making of India's constitution - Khanna , H. R. (Lucknow, 1981)
There are few men that make history. Justice H.R. Khanna, former Justice of the Supreme Court, is one of those great men, who stood up for dharma, the rule of law, and the individual, at great personal cost, in perilous times when the primacy of the rule of law and the strident independence of the judiciary that is taken for granted today, had been put in jeopardy. He did so by dissenting in the Habeas Corpus case, ADM, Jabalpur v. Union of India, (1976) 2 SCC 521, against the then overmighty executive, during a time when the Constitution itself was in great peril. "The New York Times" observed in an editorial dated April 30, 1976 If India ever finds its way back to freedom and democracy, that proud hallmark of its first 18 years, someone will surely erect a monument to Justice H.R. Khanna of the Supreme Court. 'His great dissenting opinion in the Habeas Corpus case and his pivotal opinion in Kesavananda Bharati, (1973) 4 SCC 225 read with the opinion in Indira Nehru Gandhi case, 1975 Supp SCC 1 laying down the Basic Structure doctrine, are as constitutive of India's Constitution as the text of the Constitution of India. This book was originally a compilation of three lectures delivered by Justice H.R. Khanna on the making of India's Constitution. With the objective of presenting a more holistic understanding of Justice Khanna's contribution to the making of India's Constitution, the present edition has been thoroughly revamped. Justice Khanna's above mentioned opinions in Kesavananda Bharati v. State of Kerala, (1973) 4 SCC 225; Indira Nehru Gandhi v. Raj Narain, 1975 Supp SCC 1 and ADM, Jabalpur v. Union of India, (1976) 2 SCC 521 have been included along with the relevant headnotes in this edition. The present book is a must-have for all those who strive towards a better understanding of the Constitution of India. At the same time, all those who hold the eminent Justice Khanna in high esteem would find the compilation to be a proud addition to their library. Also, to gain further in-roads into the opinions and views of Justice Khanna, his autobiography "Neither Roses Nor Thorns" [1987 Edition, Reprinted 2003], will be a great asset.
Keywords: Constitutional law